Respuesta :
The given expression is
2 ln a + 2 ln b - ln a
It simplifies to
ln a + ln b² = ln ab²
Let us check the given answers.
1. ln ab² - ln a = ln (ab²)/a = ln b²
FALSE
2. ln a + 2 ln b = ln ab²
TRUE
3. ln a² + ln b² - ln a = ln (a²b²)/a = ln ab²
TRUE
4. 2 ln ab = ln a²b²
FALSE
5. ln ab²
TRUE
Answer:
Choices 2, 3, and 5 are correct.
2 ln a + 2 ln b - ln a
It simplifies to
ln a + ln b² = ln ab²
Let us check the given answers.
1. ln ab² - ln a = ln (ab²)/a = ln b²
FALSE
2. ln a + 2 ln b = ln ab²
TRUE
3. ln a² + ln b² - ln a = ln (a²b²)/a = ln ab²
TRUE
4. 2 ln ab = ln a²b²
FALSE
5. ln ab²
TRUE
Answer:
Choices 2, 3, and 5 are correct.
Equivalent expressions are expressions with equal values
The equivalent expressions are: (2) ln a + 2 ln b, (3) ln a2 + ln b2 - ln a and (5) ln ab2
The expression is given as:
2 ln a + 2 ln b - ln a
Collect like terms
2 ln a + 2 ln b - ln a = 2 ln a - ln a + 2 ln b
Evaluate the like terms
2 ln a + 2 ln b - ln a = ln a + 2 ln b
Also, we have:
2 ln a + 2 ln b - ln a = 2 ln a - ln a + 2 ln b
Apply law of logarithm
[tex]2\ln a + 2\ ln b - \ln a = \ln a^2 - \ln a + \ln b^2[/tex]
Apply law of logarithm
[tex]2\ln a + 2\ ln b - \ln a = \ln \frac{a^2 * b^2}{a}[/tex]
Simplify
[tex]2\ln a + 2\ ln b - \ln a = \ln ab^2[/tex]
Hence, the equivalent expressions are:
(2) ln a + 2 ln b, (3) ln a2 + ln b2 - ln a and (5) ln ab2
Read more about equivalent expressions at:
https://brainly.com/question/2972832